Outcome of Arthroscopic Dorsal Peripheral Repairs of the Triangular Fibrocartilage with a Positive Hook Test and an Intact Foveal Ligament - Ecker, Jeff; Pavleski, Karolina; de Jong, Jess; Jones, Zoe; Andrijich, Courtney (Journal of Wrist Surgery, 2025)
This study was performed to determine whether an arthroscopic dorsal peripheral triangular fibrocartilage complex (TFCC) repair can stabilize symptomatic distal radioulnar joint (DRUJ) instability in patients with a positive hook test, an intact foveal insertion, and a dorsal peripheral detachment of the TFCC.All patients who had an isolated arthroscopic dorsal peripheral TFCC repair performed by the primary author between August 2018 and April 2023 were included in the study. Functional measures of range of motion (ROM), gross grip, lateral pinch, force plate, pronation strength, supination strength, visual analogue scale (VAS) at rest, VAS on use, patient rated wrist evaluation (PRWE), and disabilities of the arm, shoulder, and hand (DASH) were recorded pre- and postoperatively.For this study 31 patients met the inclusion criteria. Measures taken at a mean of 13.8 months post-surgery demonstrated improvement in all functional parameters, with the exception of ulnar deviation and pronation which remained unchanged. Resolution of symptomatic DRUJ instability was documented in all cases. There were no cases of recurrent instability. There were no complications.Arthroscopic dorsal TFCC repair can successfully resolve symptomatic DRUJ instability in patients with a positive hook test, a dorsal peripheral detachment of the TFCC, and an intact foveal insertion.Level IV
Keywords: triangular fibrocartilage; hook test; dry arthroscopy; wrist; distal radioulnar joint; arthroscopic repair